Anaplastic Large Cell Lymphoma Occurring in an HIV-Positive Patient - Genet, Philippe; Chaoui, Driss; Masse, Virginie; Al Jijakli, Ahmad; Arakelyan, Nina; Sutton, Laurent (Case Reports in Hematology, 2012)
Cases of anaplastic large-cell lymphoma (ALCL) of T phenotype are sparse in the setting of HIV patients. We report herein a case of T-ALCL, with an advanced stage, pulmonary involvement, high HIV viral load, and low CD4 level. Anaplastic lymphoma kinase (ALK) protein expression was negative. Anthracyclin-based chemotherapy was unsuccessful. The literature review was performed focusing on incidence, clinical characteristics, prognosis, and physiopathology of ALCL in HIV patients. More data are needed to improve the knowledge of such cases and to define a better treatment approach.